Poor sleep is associated with sensation-seeking and risk behavior in college students - Laila Taghvaee; Amir Ali Mazandarani (Sleep Science)
Objective: The current study examines the relationship between sleep duration and variability with sensation- seeking and risky behaviors in a sample of Iranian undergraduate students. Methods: The participants in this study were 385 undergraduate students in Tehran. To collect data, we used the Sensation Seeking Scale, Risk Behavior Scale, and two questions related to sleep duration and sleep variability. Results: The results showed a positive relationship between sleep deprivation and irregular sleep schedule with sensation-seeking and risk behavior tendencies in students. Discussion: This association could point to an indirect impact of sleep deprivation on sensationseeking and risk behavior, for example, by altering brain regions responsible for self- control.